Risk of transition to lead-free in the space sector: Sn whisker growth in thermal vacuum conditions from submicron Sn layer - Balázs Illés; Agata Skwarek; Tamás Hurtony; Olivér Krammer; Bálint Medgyes; Krzysztof Szostak; Gábor Harsányi; András Kovács; Béla Pécz (Materials & Design)
Sn whisker growth was investigated from submicron Sn layers on Cu substrates in thermal vacuum conditions to compare the growth differences in ambient and space conditions. Cu substrates were covered with 500 nm thick Sn by PVD. The samples were kept at 50 °C and 8.3x10-6 mbar for 1000 h in order to simulate the space conditions. Numerous Sn whiskers were found on the samples after some days of sample preparation. More but shorter whiskers with different structures were developed in a vacuum than in ambient conditions before. The vacuum-grown whiskers had segmented block-like bodies with a plain surface, while ambient-grown whiskers had a twisted body with grooves. TEM investigations found a weak correlation between the crystal structure and the shape of the different whiskers. However, it proved that the high mechanical stress of the Cu6Sn5 intermetallic layer growth initiated the interface flow mechanism, which transported Cu6Sn5 into the whiskers. The vacuum-grown whiskers contained approximately half the amount of Cu6Sn5 inclusions than the ambient-grown ones, which could be related to the more uniform stress relaxation of the oxide-free surface in the vacuum. The higher amount Cu6Sn5 inclusions could cause the twisting of the whisker bodies in ambient conditions.